2009
DOI: 10.1128/jcm.01991-08
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Pyrosequencing in Identifying Bacteria Directly from Positive Blood Culture Bottles

Abstract: Growth in liquid media is the gold standard for detecting microorganisms associated with bloodstream infections. The Gram stain provides the first clue as to the etiology of infection, with phenotypic identification completed 1 or 2 days later. Providing more detailed information than the Gram stain can impart, and in less time than subculturing, would allow the use of more directed empirical therapy and, thus, reduce the patient's exposure to unnecessary or ineffective antibiotics sooner. The study had two ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…Of the six different DNA purification methods tested by Fredricks et al, 9 only a benzyl alcoholguanidine hydrochloride organic extraction method generated extracts that were pure enough to be used undiluted in PCR and in pyrosequencing for pathogen identification. 40 Although a direct comparison between the benzyl alcohol extraction method and the Automate Express chemistry was not performed for the present study, both are able to generate extracts that can be directly used in PCR assays. Of lesser importance, Fredricks et al 9 reported that phenol-chloroform extracts require 1000-fold dilution to achieve inhibition-free PCR, whereas in the present study only 10-fold to 100-fold dilutions were required, depending on the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six different DNA purification methods tested by Fredricks et al, 9 only a benzyl alcoholguanidine hydrochloride organic extraction method generated extracts that were pure enough to be used undiluted in PCR and in pyrosequencing for pathogen identification. 40 Although a direct comparison between the benzyl alcohol extraction method and the Automate Express chemistry was not performed for the present study, both are able to generate extracts that can be directly used in PCR assays. Of lesser importance, Fredricks et al 9 reported that phenol-chloroform extracts require 1000-fold dilution to achieve inhibition-free PCR, whereas in the present study only 10-fold to 100-fold dilutions were required, depending on the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies combining a multiplex PCR with different types of identification of amplicons have shown good correlation with cultures [49][50][51]. However, these expensive amplification techniques will probably not be used when starting from positive blood culture bottles.…”
Section: Detection Of Pathogens In Positive Blood Culturementioning
confidence: 99%
“…In the present study, the rate of concordance between the two techniques was lower. This was partly because a larger number of polymicrobial samples were included in the present study than were present in the study by Jordan et al (2009). Furthermore, the relatively large number of specific strains that went undetected, such as members of the genus Enterobacter, could also decrease the rate of concordance of this study.…”
Section: Discussionmentioning
confidence: 46%
“…Highly accurate pyrosequencing identification of bacteria from positive blood culture bottles has been reported previously (Jordan et al, 2009). In this report, the 23S rRNA gene was used as the target to improve the accuracy of identification of some specific bacteria, such as members of the family Enterobacteriaceae and the genus Streptococcus, and the agreement between the results of pyrosequencing-and culture-based identification reached 97.8 %.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation